Vibrational spectroscopy in combination with chemometrics as an emerging technique in the authentication of coffee: A review - David Fernando, Anindya Rahmanina, Abdul Rohman, Djoko Santosa (Journal of Applied Pharmaceutical Science, 2023)
Coffee enthusiasts now consume coffee not only as a reliever of drowsiness but also as a lifestyle. Sizeable annual consumption and high demand for exports of coffee can trigger a shortage of coffee stocks from supply companies. This shortage has forced some producers to take fraudulent actions in coffee counterfeiting. With the vast economic benefits of substituting or adulterating coffee, the development of authentication methods is an ideal solution to follow up on this practice. The combination of some chemometric methods including pattern recognition and multivariate calibrations with fingerprint analysis techniques of Fourier transform infrared spectroscopy (FTIR) spectroscopy could be performed to authenticate coffee products. The use of chemometrics is unavoidable because of the large amount of data received even from the single scanning of FTIR spectra. Some chemometric methods are commonly applied to build classification and prediction models of adulterants in coffee. The objective of this review is to feature the application of infrared (IR) spectroscopy and chemometric analysis to authenticate coffee from various adulterants.
Keywords: Coffee, authentication analysis, IR spectroscopy, chemometrics, Raman spectroscopy